Risk factors for infections and secondary malignancies in patients with a myeloproliferative neoplasm treated with ruxolitinib: a dual-center, propensity score-matched analysis. Issue 3 (23rd February 2020) - Tremblay, Douglas; King, Amber; Li, Lihua; Moshier, Erin; Coltoff, Alexander; Koshy, Anita; Kremyanskaya, Marina; Hoffman, Ronald; Mauro, Michael J.; Rampal, Raajit K.; Mascarenhas, John
Abstract: Ruxolitinib is a JAK1/2 inhibitor approved for the treatment of myelofibrosis (MF) and polycythemia vera (PV). Recent data have suggested the possibility of increased infectious and secondary malignancy rates in patients treated with ruxolitinib. We conducted a dual-center, retrospective study of 202 myeloproliferative neoplasm (MPN) patients receiving ruxolitinib and a control cohort of 73 ruxolitinib-naïve MPN patients. We utilized propensity score matching to analyze the primary outcome of development of any grade infection. Infections occurred in 38.4% of ruxolitinib-naïve patients and 42.6% of ruxolitinib-treated patients and were primarily grade 1/2. After propensity score weighting, there was no difference in risk of infection between ruxolitinib-treated and -naïve patients with MF (HR 1.15 [95% CI 0.80–1.65], p  = .466) and non-MF MPNs (HR = 0.52 [95% CI 0.21–1.28, p  = .152). These results suggest that there is not an increased risk of infection with ruxolitinib therapy.